PSYCHOLOGICAL FEATURES OF CREATIVE THINKING IN PERSONALITY DEVELOPMENT (American Journal of Interdisciplinary Research and Development, 2023)
The article considers the features of mental operations. Particular importance is attached to the role of creative thinking in the development of the individual and tasks that would help prepare students for creative activities and the formation of appropriate intellectual skills.